The College Union: Where Tradition Meets Decolonization on Campus (Open Rivers, 2023)

(untitled)
Higher education has undergone many changes since the first colleges in the old world came to be. Institutions of higher learning respond to societal pressures and needs, which means that education is ever evolving and dependent on the social context in which institutions find themselves. However, there is no denying that the first institutions of higher learning were not welcoming places for people not of the elite classes. These institutions were, and are, places where the education of future leaders has been the premier goal (Cohen and Kisker 2010). To achieve this goal, institutions of higher learning have employed a mixture of curricular, extra-curricular, and co-curricular tools...